Causal relationship between varicose veins and hydrocele: A bidirectional two-sample Mendelian randomization study - Chunzhi Guo; Yan Qu; Hong Liu (SAGE Open Medicine, 2025)
Objective: This study aimed to investigate the causal relationship between varicose veins and hydroceles. Methods: Genetic data for varicose veins and hydroceles were extracted from a Genome-Wide Association Study (GWAS). A total of 22,037 cases of varicose veins and 2634 cases of hydroceles were included for Mendelian randomization analysis. Inverse variance-weighted (IVW) analysis was employed as the primary method, with weighted median and MR-Egger analyses were used for supplementary validation. Several sensitivity analyses were performed to further assess the results. Results: The IVW analysis of varicose veins on hydroceles revealed an odds ratio (OR) of 1.117 (95% confidence interval (CI), 1.009–1.236; P  = 0.014). Conversely, the IVW analysis of hydroceles on varicose veins showed an OR of 0.983 (95% CI, 0.944–1.025; P  = 0.330). Heterogeneity and pleiotropy were negative in the bidirectional analysis. Conclusions: This study suggests that varicose veins may be a risk factor for hydroceles. However, there is no evidence to support hydroceles as a causal risk factor for varicose veins. Our findings provide genetic evidence for the potential role of varicose veins as a risk factor for hydroceles, offering new insights for clinical practice. By establishing the causal relationship, high-risk patients can be identified, allowing for early surveillance of hydrocele presence to facilitate timely intervention and optimized treatment strategies. A statistically significant causal relationship between varicose veins and hydroceles was found, whereas hydroceles did not exert a causal impact on varicose veins.